การติดตามอาการอันไม่พึงประสงค์จากการใช้ยาต้านมะเร็งของผู้ป่วยใน ณ โรงพยาบาลมหาราชนครเชียงใหม่ - นราวดี ประเสริฐวิทยากิจ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives of this research were to study rates, characteristics and cost of treatment on adverse drug reaction (ADRs) in patients treated with antineoplastic drugs as well as the effects of pharmacist s counseling to these patients. The study was performed during December 1998 to May 1999 at the medicine wards or orthopedic wards, Maharaj Nakorn Chiangmai Hospital. The detection of ADRs was based on the abnormal laboratory tests and clinical signs and symptoms. Direct medical costs for treating ADRs were assessed according to the hospital charges. Seventy-one patients were monitored for ADRs, their average age was 48.8 years. Most of the patients (94.4%) were treated with 2 antineoplastic drugs, 1,174 problem of ADRS were found in which 2.5 problems occurred every single time of drug used. Reactions to the gastrointestinal system were the most adverse reactions involved the patients (38.8%) such as nausea, vomiting and mucositis. The second were hematological system (38.3%) such as anemia, leukopenia and thrombocytopenia, effects on dermatological system were 8.8%, followed by neuromuscular system (4.3%). The severity of the reactions classified as grade 1, 2 was found in 87.5% of the pateints where as the rest (12.5%) was grade 3, 4 which needed to be treated or prolong hospitalization, these reactions were anemia, leukopenia induced sepsis and severe emesis. Leukopenia was also the cause of postponement for the next antineoplastic treatment regiment. Five patients had to discontinue their current treatment regimen because of renal dysfuction. The total cost for treatment of ADRs in this study was 116,167 baht where the average cost was 250 baht to once antineoplastic drug was used. After being counseling on antineoplastic drug uses, the patients showed significantly increased (p<0.05) in knowledge about antineoplastic drugs and about management or avoidance of drug toxicity. All of patients were satisfied with the counseling program and agreed that this service should be performed continuously.